Multiple Forms of Prewriting in Elementary Writing Lessons - Carolyn L. Piazza; Christine Jecko (Journal of the Assembly for Expanded Perspectives on Learning, 2003)
Multisensory prewriting invitations (creative visualizations, art, music, dreams, and mediations) affect writing fluency and idea generation in the first draft writing of elementary students.